Basic Universe of Molecular Electronics System (MES): Introduction and its Applications in Harvesting Daily Life - Hendry Izaac Elim (SCIENCE NATURE, 2019)
In order to understand the core of universe, one finds out a principle of molecular electronic system (MES) in which the relationship among atoms starting from a molecular system in universe structure was based on the collaborative resistance interconnection among the nearest atoms in a molecular circuit of universe, for instance in galaxy-galaxy relationship. While the whole structure of a molecule works according to their electronic circuit system. This work is quite different from the mechanical system of atomic and chemical bonding vibrations among the nearest atoms in a molecule structure that came after the formation of MES. The profits of this newly invested knowledge will open the wide impacts of universe understanding in microscopic scale up to the supergiant expanded universe. It is marvelous to state that such simple understanding can explain a complicated GOD paradox and its optics